2021
DOI: 10.1002/1878-0261.13152
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Chi3L1 antibody suppresses lung tumor growth and metastasis through inhibition of M2 polarization

Abstract: Chitinase 3‐like 1 (Chi3L1) is associated with various biological processes, such as inflammation, tissue repair, proliferation, cell survival, invasion, and extracellular matrix remodeling. Recent studies indicated that Chi3L1 is critical for cancer development and metastasis. In this study, we demonstrate that Chi3L1 serum and tissue levels were significantly increased in lung cancer patients compared with controls. We previously developed an anti‐Chi3L1‐humanized antibody, and here, we investigate its antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…For instance, the inhibitory effects of chitinase 3-like 1 on lung cancer are associated with STAT6-dependent M2 polarization inhibition. 55 A recent study found that targeting the Th2-STAT6-C3-NET (neutrophil extracellular trap) signalling axis effectively inhibited breast cancer metastasis to the lungs. 56 Another study reported that p53 mutations may promote malignancy in solitary fibrous tumours by regulating the NAB2-STAT6 fusion gene at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the inhibitory effects of chitinase 3-like 1 on lung cancer are associated with STAT6-dependent M2 polarization inhibition. 55 A recent study found that targeting the Th2-STAT6-C3-NET (neutrophil extracellular trap) signalling axis effectively inhibited breast cancer metastasis to the lungs. 56 Another study reported that p53 mutations may promote malignancy in solitary fibrous tumours by regulating the NAB2-STAT6 fusion gene at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Blotting. Cell lysis and western blotting were performed as previously described [54]. Cells were lysed with lysis bufer (20 mM Tris-HCl pH 7.8, 0.1% NP-40, 200 mM NaCl, 2 mM EDTA, 5 mM EGTA with protease inhibitor, and protease inhibitor) and centrifuged at 13,000 × g for 20 min at 4 °C.…”
Section: Cell Lysates Preparation and Westernmentioning
confidence: 99%
“…Te RT-qPCR assay was performed as previously described [54]. Total RNA was isolated using RiboEx Total RNA ( # 301-001, GeneAll Biotechnology Co., Seoul, Korea) and reverse transcribed into cDNA using the High-Capacity cDNA Reverse Transcription Kit ( # 4368813, Applied Biosystems, Foster City, CA), according to the manufacturer's protocol.…”
Section: Rt-qpcr Assaymentioning
confidence: 99%
“…Chitinase-3-like protein 1 (CHI3L1), a member of the glycoside hydrolase family 18 13 , plays crucial roles in oxidative injury, apoptosis, pyroptosis, extracellular matrix regulation, Th1/Th2 inflammatory balance, and parenchymal scarring 14 . Non-enzymatic CHI3L1 is highly expressed in various cancer types, such as lung 15 , colon, gastric, and breast cancers 16 , and is associated with low survival rates of patients with cancer. In particular, up-regulated CHI3L1 and CD44 are considered as markers of mesenchymal (MES) glioma 17 that predominantly manifested NF-κB activation 18 .…”
Section: Introductionmentioning
confidence: 99%